Some Results on Strongly*-2 Divisor Cordial Labeling (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
A strongly*-2 divisor cordial labeling of a graph  with the vertex set  is a bijection  such that each edge  assigned the label 1 if  is odd and 0 if  is even, then the number of edges labeled with 0 and the number of edges labeled with 1 differs by atmost 1. A graph which admits a Strongly*-2 divisor cordial labeling is called a Srongly*-2 divisor cordial graph. In this paper, we proved that Path, Cycle, Star and comb graph are Strongly*-2 divisor cordial graphs